Study of whiskers’ mechanical properties. creep and internal friction - Артемьев, Сергей Робленович (Technology audit and production reserves, 2014)
The results of the previously conducted studies of whiskers on the changes in properties of creep and internal friction were considered and analyzed in this paper. The results of these studies in terms of the applied load influence on them, leading to a change of crystal structure were analyzed. The conducted analysis of literature data indicates that in these and many other processes whiskers’ properties continue to be negatively influenced by the mechanical properties, including internal friction and creep. The estimation of such influence is quite important and relevant in current conditions because organometallic compounds continue to occupy a prominent place among other raw materials used in the production of metal powders, films, coatings and even finished gas-phase bulk products. Instead of huge electroplating industries and costly short-lived plants in engineering and electronic enterprises, high-output waste-free production of “small” chemistry appears. They provide not only the production of high-quality products, but also the compliance with environmental requirements for protecting human health and environment.